Dynamics of MHD Heat and Mass Transfer Past a Semi-Infinite Vertical Porous Plate in a Turbulent Boundary Layer - Ngesa, Joel O. (Zain Publications, 2018)
This study addresses the problem of unsteady free convection incompressible MHD fluid flow past a semi-infinite vertical porous plate in the presence of a strong magnetic field inclined at an angle  to the plate with Hall and Ion-Slip currents in a Turbulent boundary layer. The partial differential equations governing the flow problem considered in our study are solved by a finite difference approximation. The effects of modified Grashof number, suction velocity, the angle of inclination, time, Hall current, Ion-Slip current, Schmidt number and heat source parameter on the convectively cooled or convectively heated plate restricted to turbulent boundary layer is considered. The results show that the Hall current, Schmidt number, Modified Grashof number, heat source parameter, suction velocity, time, angle of inclination, Ion-Slip current on the convectively cooled or convectively heated plate affect the velocity, temperature and concentration profiles. Increases in Hall parameter cause a decrease in both primary and secondary profiles while increase in Ion Slip current parameter leads to increase in primary velocity profiles but a decrease in secondary velocity profiles.
Keywords: Free Convection; MHD; Turbulent flow; Semi-infinite plate; Hall and Ion-Slip currents